The music of my people: an introduction to music Barotseland - Njungu, Agrippa M. (International Library of African Music, 1960)
Music in Barotseland (the country covering most of the Zambezi Valley northwest of the Victoria Falls) penetrates and indeed completes most of our daily activities. Girls sing as they dig, pound and, above all, as they go on their several errands fetching wood, water and others. Village men, on returning from the fields, usually gather under a big tree listening to one of them playing piece after piece of music on one of our several musical instruments, while the rest work at the various crafts. The tunes on “Kangombyo” or “Kalimba” punctuate the continuous low conversational tones of the old men as they talk over many state affairs or matters of general interest.
Keywords: Ethnomusicology; Lozi (African people); Music; Rites and ceremonies; Africa; African Music; Barotseland (Northern Rhodesia); Therapeutic Use